2022
DOI: 10.1002/anie.202207150
|View full text |Cite
|
Sign up to set email alerts
|

Alcohols as Alkylating Agents: Photoredox‐Catalyzed Conjugate Alkylation via In Situ Deoxygenation

Abstract: The rapid exploration of sp3‐enriched chemical space is facilitated by fragment‐coupling technologies that utilize simple and abundant alkyl precursors, among which alcohols are a highly desirable, commercially accessible, and synthetically versatile class of substrate. Herein, we describe an operationally convenient, N‐heterocyclic carbene (NHC)‐mediated deoxygenative Giese‐type addition of alcohol‐derived alkyl radicals to electron‐deficient alkenes under mild photocatalytic conditions. The fragment coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…•− . 51−53 Indeed, a similar yield of the hydrocarboxylation product was observed from an analogous deschloro alkene substrate (9). The reaction tolerates diverse protic functional groups, including ureas (10), unprotected alcohols (11,12), carboxylic acids (13), carbamates (13), and amides (4, 7).…”
Section: •−mentioning
confidence: 70%
See 1 more Smart Citation
“…•− . 51−53 Indeed, a similar yield of the hydrocarboxylation product was observed from an analogous deschloro alkene substrate (9). The reaction tolerates diverse protic functional groups, including ureas (10), unprotected alcohols (11,12), carboxylic acids (13), carbamates (13), and amides (4, 7).…”
Section: •−mentioning
confidence: 70%
“…Alkene hydrofunctionalization methods that exploit radical intermediates are a fundamental class of synthetic reactions. Radical reactivity offers a complementary regio- and chemoselectivity profile relative to polar pathways. , Despite anti-Markovnikov hydrobromination dating back a century, , the development of radical hydrofunctionalization reactions remains a contemporary area of investigation. Our group has a particular interest in alkene hydrocarboxylation using radical intermediates. , Carboxylic acids are a readily diversifiable functional handle and are themselves a common motif found in natural products, pharmaceuticals, and commodity chemicals. We envision that a broad and general radical hydrocarboxylation reaction would offer a powerful complement to transition-metal-catalyzed methods, such as the numerous established CO-based approaches and the emerging alternative technologies that proceed through migratory insertion into CO 2 . However, established approaches to radical hydrocarboxylation have remained largely limited to activated alkenes (Figure A). ,, Unactivated aliphatic alkenes are an abundant and important substrate class but remain more challenging to engage due to their attenuated reactivity. Indeed, in the past year, Yu and co-workers reported the first and only synthetic methodology that engages unactivated alkenes with CO 2 •– .…”
mentioning
confidence: 99%
“…However, the direct use of native alcohols as cross-coupling partners is an unrealized goal. Recent work from our group has uncovered a solution to this problem: we have introduced an N-heterocyclic carbene (NHC)-derived reagent capable of activating alcohols in situ and transforming them into alkyl radicals through photoredox catalysis. We envisioned utilizing this novel activation mode to unlock unprecedented sp 3 -rich chemical space by coupling ubiquitous alcohols with bench-stable, commercially abundant alkyl bromides through nickel metallaphotoredox catalysis (Figure d). A key goal of this work is to forge bonds between two secondary sp 3 centers.…”
mentioning
confidence: 99%
“…Numerous photoredox catalytic methods have emerged to activate alcohols for homolytic cleavage of C­(sp 3 )–O bonds . However, the developed approaches are either not amenable to primary alcohols for generation of nonstabilized alkyl radicals or require noble metal photocatalysts . Very recently, we revealed that a xanthate anion can be directly excited by visible light and exhibits strong reducing ability in its excited state (* E 1/2 red < −2.4 V vs SCE) .…”
mentioning
confidence: 99%